Slumpbuster - Markey, Kevin (Super Sluggers, 2009)
Eleven-year-old slugger Banjo "The Great Walloper" Bishbash is overcome by a nasty hitting slump as he tries to lead the Rambletown Rounders to the division baseball championship.